Study of deuteron spectra under radiation belt with PAMELA instrument. (July 2015) - Koldobskiy, S A; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; Cafagna, F; et al.
Abstract: This paper presents the results of measurements of proton and deuteron fluxes of albedo radiation in the Earth vicinity, obtained in the PAMELA experiment. PAMELA is an international experiment meant to study cosmic rays. PAMELA is carried out on board the satellite Resurs-DK1. High-precision equipment of the experiment allows registration and identification of cosmic ray particles of different varieties in a wide energy range. The albedo deuteron spectrum and albedo deuteron-to-proton fluxes ratio in the energy range 70 – 600 MeV/nucleon at altitude of 350 – 600 km for different geomagnetic latitudes is presented.